2011
DOI: 10.1002/ijc.26298
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain is not selectively decreased in murine cancer cachexia

Abstract: Cachexia is a severe muscle-wasting syndrome associated with several chronic diseases such as cancer and AIDS. Muscle mass loss significantly decreases prognosis and survival. The mechanisms of muscle atrophy and the specific proteins targeted for degradation have been intensely studied and are potential therapeutic targets. Published reports that myosin heavy chain (MyHC), the most abundant protein by mass in skeletal muscle, is selectively targeted for degradation in cancer cachexia remain controversial. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 28 publications
2
38
2
Order By: Relevance
“…To determine whether this impairment is related to alterations in myofibrillar protein expression, we quantified MyHC and actin protein levels. Samples were processed in a high‐salt lysis buffer since a recent study clearly demonstrated their significantly greater solubility, and, therefore, more accurate quantification, when processed in this buffer (26). Normalized to total protein within the solubilized fraction, MyHC levels were decreased by 27% in the diaphragm of C‐26 mice compared to controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether this impairment is related to alterations in myofibrillar protein expression, we quantified MyHC and actin protein levels. Samples were processed in a high‐salt lysis buffer since a recent study clearly demonstrated their significantly greater solubility, and, therefore, more accurate quantification, when processed in this buffer (26). Normalized to total protein within the solubilized fraction, MyHC levels were decreased by 27% in the diaphragm of C‐26 mice compared to controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This normally provides a strong mechanical link between the intracellular cytoskeleton and extracellular matrix 29. It is also thought that there is selective targeting of myofibrillar proteins, in particular MyHC, in cancer cachexia7,10 although a single study has suggested that the selective breakdown of MyHC in mice with cancer may be artefactual 30. In addition, myofibrillar degradation appears to occur in a time-dependent manner 21.…”
Section: Discussionmentioning
confidence: 99%
“…For optimal extraction and processing of MHC and actin, muscles were homogenized in a high-salt lysis buffer as described previously (Cosper and Leinwand, 2012;Roberts et al, 2013b). Samples were mixed in Laemmli buffer (Bio-Rad, Hercules, CA) and heated.…”
Section: Contractile Protein Analysesmentioning
confidence: 99%